The issues of legal regulation of condominiums - Старицька, О. О.; Польська, М. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article the authors analyze a modern status of legal regulation institute condominiums. On the basisof this analysis were singled out issues of functioning housing sector, and suggested solutions.